Mapping The Old Kampongs Along The Gajahmada Road - Dewi, Diah Intan Kusumo; Kurniawati, Wakhidah; Nurini, Nurini; Islamey, Talitha Zuleika (Jurnal Teknik Sipil dan Perencanaan, 2020)
Abstract. The old kampongs along Gajahmada Road are one of the oldest sections in Semarang City. The existence of the old kampongs can be seen on the map in 1900. However, the old Kampongs changed their environmental conditions considerably due to their commercial activities, especially in 2007. The existence of high-rise commercial buildings dominates corridors along the Gajahmada road, and the presence of old kampongs located behind the buildings is also displaced. Whereas, the presence of these old kampongs keeps a history of the development of Semarang City and traditional houses. This article seeks to identify changes in the appearance of the old kampongs which are displaced due to the development of the commercial activity, based on a field survey, map analysis, building form and street analysis. There are significant changes and minor changes that occurred in the old kampongs along Gajahmada road. Physical changes that occur are changes in land use, ways and building functions.